PENGARUH EKSPOR MINYAK MENTAH DAN EKSPOR GAS TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Kambono, Herman (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study aims to determine the effect of the export value of oil and gas commodities, crude oil exports, and gas exports on economic growth in Indonesia. The independent variables in this study are crude oil exports, gas exports, and exports. While the dependent variable in this study is economic growth as measured by looking at Indonesia's GDP data. This type of research uses a quantitative method with a sample using purposive sampling. The data used in this study is data obtained indirectly (secondary) through intermediaries or internet media. Data analysis in this study uses descriptive analysis, classical assumption tests, multiple linear regression analysis and hypothesis testing using the SPSS program.Theresults of this study will show whether the value of crude oil exports and gas exports have a partial or no effect on economic growth in Indonesia. And whether the two product exports do not have a simultaneous effect on economic growth in Indonesia for the 2012-2021 period, or vice versa.